Factors influencing the deterioration of traditional madrasahs’ performance in Zanzibar: The teachers’ experiences - Malengo, Ali Faki; Md. Noon, Hazizan (The International Journal Of Humanities & Social Studies, 2017)
This qualitative study was carried out to examine the factors influencing the deterioration of traditional madrasahs’ performance in Zanzibar. In addition, the study also sought to analyse the measures which were taken to address those factors. Four male and two female experienced teachers from three different madrasahs were purposely selected as the respondents. Semi-structured in-depth interview was used to collect primary data while secondary data source included the relevant documents such as official documents, journals articles, and proceedings. The interviews were transcribed, coded, classified and then analysed. The content analysis method was used for analysing the documents. The findings of this study showed that traditional madrasahs’ performance in Zanzibar was deteriorating. Although some efforts have been taken by the Madrasahs to address the problem, the intended performance did not seem to be up to the expectation. Based on these findings, it is recommended that all stakeholders should play more effective role to solve the problems that hinder the attainment of such performance.